HEALTH RELATED QUALITY OF LIFE AFTER BURNS: ARE WE REALLY TREATING BURNS? - Tahir, Syed Mohammed; Memon, Mohammed Munir; Ali, Syed Asad; Rasheeed, Saadia (Journal of Ayub Medical College Abbottabad, 2011)
Background: During the last few decades management of burns has undergone positive revolutionary change. Today, over 50% of all patients with burns involving 80% of their total body-surface area can survive. Although the objective assessment by attending physician can well define a patient’s degree of health, the patient’s subjective perceptions and expectations that can influence burn survivors’ experience of their life is much more important. Methods: Adult burn patients of both sexes admitted to burn unit with major burns either by size or site who required reconstruction for burn injury were the subjects of this study. The health related quality of life was assessed using SF-36v2®, questionnaire. Results: The mild to moderate pain complaint by 87 (88%) of all burn survivors, badly impact role physical and general health with resultant decrease in physical component summary. What was more difficult to explain was the decreased mental health which is evident soon after the incidence and persisted throughout the period of follow-up, showing statistically insignificant improvement when compared from basal score (p=0.008). Longitudinal decline in HRQoL had strong relationship with female sex, involvement of prime area, hospital admissions, hospital stay and sessions of surgery. Sex, occupation, involvement of prime area and hospital admissions, were the important predictors for decrease in physical component summary of burn survivors. Involvement of prime area and hospital admissions were important determinant for decrease in mental component summary. Conclusion: The level and quality of multidisciplinary rehabilitation that these victims needs is very low as compared to developed countries. These patients need long term professional, psychological, and social support. Keywords: Quality of Life, Burn Survivors, Health related Quality of Life, subjective health